Association between the practice of fitness-related exercises and body image dissatisfaction in adolescents from Curitiba (PR), Brazil - Rinelly Pazinato Dutra; Yasmin Marques Castro; Maria Eduarda Santos de Almeida; Letícia Lamberty Pedrozo; João Venícios Tavares de Sousa; Murilo Bastos; Wagner de Campos; Michael Pereira da Silva (Sociedade de Pediatria de São Paulo, 2024)
ABSTRACT Objective: The aim of this study was to analyze the association between participation in fitness-related exercises (FRE) and body image dissatisfaction (BID) in adolescents and evaluate the interaction between physical exercise and nutritional status in this association. Methods: A cross-sectional study was conducted in 2015 involving 799 adolescents (10-16 years old) from 14 public schools in Curitiba (PR), Brazil. BID was assessed using the Body Shape Questionnaire and the Silhouette Scale. The FRE was classified as "does not practice," "practices ≤300 min/week," and "practices >300 min/week" by the Physical Activity Questionnaire for Adolescents. Poisson and multinomial logistic regressions, adjusted for sex, sexual maturation, and nutritional status analyzed the association of FRE and BID. Results: The BID prevalence was 28.3%; 52.4% of the adolescents wanted to reduce their silhouettes; and 48.7% did not practice FRE. Adolescents who practiced FRE >300 min/week had a 28% higher prevalence for some level of BID (PR 1.28; 95%CI 1.08-1.52) and a 46% lower chance of wanting to reduce silhouettes (OR 0.54; 95%CI 0.35-0.82), compared to nonpractitioners. There was no interaction between FRE and nutritional status in association with BID. Conclusions: The adolescents who practice FRE >300 min/week are likely to have some level of BID and are less likely to report the desire to increase their silhouettes, regardless of their nutritional status.